Design and development of cocoa pod breaking and beans extraction machine - Fonsso JosuÃ©, Dzudie; Mbetmi Guy-De-Patience, Ftatsi; Bienvenu, Kenmeugne; Bonaventure, Djeumako (International Journal of Engineering and Technology, 2019)
The cocoa bean damage is one of the main problems of pod breaking process. Beans damage, separation of beans from mixtures and scrap shells are the main problems related to cocoa pod breaking. The objective of this work is to determine the physical and mechanical properties of cocoa pods required for the design of the equipment, dimension of the different parts constituting the equipment and put in place a geometric representation of the equipment that can rise the quality of cocoa products. Some physical and mechanical properties of the pod where obtained through experimental study. Different varieties of cocoa were initially subjected to compressive forces along the lateral axis. After that, they were set on a test bench to break the pods one after the other with a mass of steel at different heights. Thus, the average breaking strength and the moisture contents of each variety of cocoa pods were determined. This fracture resistance of the cocoa pod was measured in terms of average force, deformation and toughness at the cocoa shell fracture, and cocoa pod stiffness (rigidity). The modulus of rigidity of the pod was obtained from measurements of force and deformation. From the physical and mechanical properties of the pod, we modelled a suitable machine. This designed machine severs the poles and ruptures the pods facilitating extraction of the beans on the hulls. It can be assembled and disassembled easily, reliably and without any risk for the user. Consequently, it might be used by all cocoa producers in other to optimize the process of cocoa pod breaking.Â Â